MORN5 Expression during Craniofacial Development and Its Interaction with the BMP and TGFβ Pathways - Cela, Petra; Hampl, Marek; Fu, Katherine K.; Kunova Bosakova, Michaela; Krejci, Pavel; Richman, Joy M.; Buchtova, Marcela (Frontiers in Physiology, 2016)
MORN5 (MORN repeat containing 5) is encoded by a locus positioned on chromosome 17 in the chicken genome. The MORN motif is found in multiple copies in several proteins including junctophilins or phosphatidylinositol phosphate kinase family and the MORN proteins themselves are found across the animal and plant kingdoms. MORN5 protein has a characteristic punctate pattern in the cytoplasm in immunofluorescence imaging. Previously, MORN5 was found among differentially expressed genes in a microarray profiling experiment of the chicken embryo head. Here, we provided in situ hybridization to analyse, in detail, the MORN5 expression in chick craniofacial structures. The expression of MORN5 was first observed at stage HH17-18 (E2.5). MORN5 expression gradually appeared on either side of the primitive oral cavity, within the maxillary region. At stage HH20 (E3), prominent expression was localised in the mandibular prominences lateral to the midline. From stage HH20 up to HH29 (E6), there was strong expression in restricted regions of the maxillary and mandibular prominences. The frontonasal mass (in the midline of the face) expresses MORN5, starting at HH27 (E5). The expression was concentrated in the corners or globular processes, which will ultimately fuse with the cranial edges of the maxillary prominences. MORN5 expression was maintained in the fusion zone up to stage HH29. In sections in situs, MORN5 expression was localised preferentially in the mesenchyme. We examined signals that regulate MORN5 expression in the face based on a previous microarray study. Here we validated the array results with in situ hybridization and QPCR. MORN5 was downregulated 24h after Noggin and/or RA treatment. We also determined that BMP pathway genes are downstream of MORN5 following siRNA knockdown. Based on these results, we conclude that MORN5 is both regulated by and required for BMP signalling. The restricted expression of MORN5 in the lip fusion zone shown here supports the human genetic data in which MORN5 variants were associated with increased risk of non-syndromic cleft lip with or without cleft palate.